Pengaruh Metode Think Pair Share dalam Meningkatkan Kemampuan Asking and Giving Suggestion - Firmansyah, Firmansyah (Yayasan Sembilan Pemuda Indonesia, 2022)
This study aims to determine the effect of applying the Think Pair Share method to improve English speaking skills in the asking and giving suggestion material for students in class XI IPA 1 in the odd semester of the academic year 2021/2022. This research belongs to the type of classroom action research with reference to the Kemmis and Mc Taggart model with the procedures for planning, implementing, evaluating, and reflecting. This study involved 40 students (31 female students and 9 male students) as research subjects. This classroom action research uses 2 cycles, each cycle consists of 2 meetings. The results of data analysis in the first cycle of the first meeting resulted in an average score of 67.8. The results of data analysis in the first cycle of the second meeting resulted in an average score of 71.3. The results of the data analysis of the first cycle of 2 meetings resulted in an average score of 75.4. The results of data analysis in the second cycle of the second meeting resulted in an average score of 77.5. The results of this study indicate that the use of the think pair share method can improve English speaking skills in asking and giving suggestion materials to Class XI Science 1 Language Odd Semester MAN 1 Muara Enim Academic Year 2021/2022.